A liquid-phase continuous-flow peptide synthesizer for preparing C-terminal free peptides. Issue 4 (11th January 2023) - Otake, Yuma; Adachi, Kyohei; Yamashita, Yoshiaki; Iwanaga, Natsumi; Sunakawa, Hirokatsu; Shamoto, Taiki; Ogawa, Jun-ichi; Ito, Atsushi; Kobayashi, Yutaka; Masuya, Keiichi; Fuse, Shinichiro; Kubo, Daisuke; et al.
Abstract : An automated continuous-flow liquid-phase peptide synthesizer for preparing C-terminal free peptides was developed. This system includes aqueous workup, concentration, and in-line NIR monitoring. Abstract : Despite the importance of peptide drugs, their production has been usually performed by unsustainable and time-consuming methods. Conventional peptide production requires repeated amidation and deprotection steps that increase the amount of waste and the time and effort required. Therefore, in this study, we developed an automated continuous-flow liquid-phase peptide synthesizer for the preparation of C-terminal free peptides for the first time. Our synthesizer comprises an amidation unit with a micro-flow reactor, an extraction unit with mixer settlers, a concentration unit with a thin-layer evaporator, and a control unit. A crude dipeptide, Fmoc-Ala-Phe-OH, and a tripeptide, Fmoc-Ala-Phe-Phe-OH, that was directly obtained from the crude dipeptide, were synthesized using our system. The steadiness of the flow system was continuously monitored by measuring the process parameters, namely the flow rate, pressure, and temperature. The peptide synthesis was monitored using a near-infrared (NIR) sensor. Our strategy enabled the first liquid-phase continuous-flow peptide synthesis, including aqueous workup and concentration, and the in-line NIR monitoring of peptide-bond formation. Thus, it will contribute to enhancing efficiency in peptide production.